2011
DOI: 10.1007/s10600-011-9896-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biologically active constituents of Salsola collina

Abstract: A new natural product (N-acetyltryptophan), together with 22 known constituents, including seven alkaloids, six flavonoids, six organic acids, and other compounds, were isolated from Salsola collina Pall. Their structures were elucidated on the basis of chemical reaction and spectral evidence. Among the isolated compounds, N-acetyltryptophan (8) showed moderate inhibition of D-amylase activity, and terrestric acid (9) showed positive antifungal activity.Salsola collina Pall., which is widely distributed in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…In this study, we discovered that transgenic expression of the herbicide-resistance enzyme BAR of bacterial origin indeed acetylate two endogenous amino acids, resulting in the ectopic accumulation of acetyl-aminoadipate and acetyl-tryptophan. While acetyl-tryptophan is a naturally occurring metabolite found in numerous plant species, including Arabidopsis, Salsola collina , Glycine max , Solanum lycopersicum , Cocos nucifera , and Ginkgo biloba 24,25 , to the best of our knowledge, acetyl-aminoadipate has never been reported as an endogenous plant metabolite. Interestingly, in line with our findings, a recent study reported the ectopic accumulation of acetyl-aminoadipate in the flower tissue of a BAR-containing T-DNA mutant of Arabidopsis, which could not be rationalized by the mutated gene 26 .…”
mentioning
confidence: 93%
“…In this study, we discovered that transgenic expression of the herbicide-resistance enzyme BAR of bacterial origin indeed acetylate two endogenous amino acids, resulting in the ectopic accumulation of acetyl-aminoadipate and acetyl-tryptophan. While acetyl-tryptophan is a naturally occurring metabolite found in numerous plant species, including Arabidopsis, Salsola collina , Glycine max , Solanum lycopersicum , Cocos nucifera , and Ginkgo biloba 24,25 , to the best of our knowledge, acetyl-aminoadipate has never been reported as an endogenous plant metabolite. Interestingly, in line with our findings, a recent study reported the ectopic accumulation of acetyl-aminoadipate in the flower tissue of a BAR-containing T-DNA mutant of Arabidopsis, which could not be rationalized by the mutated gene 26 .…”
mentioning
confidence: 93%
“…Only about 60 biological active ingredients have been detected from S. collina, including flavonoids, alkaloids, phenolic acids, organic acids, sterols, etc. [ 6 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The main compounds are flavonoids and phenolic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The main compounds are flavonoids and phenolic acids. The 18 reported flavonoids mainly involve flavones, flavonols and isoflavones [ 6 , 14 , 17 , 18 , 19 , 20 ]. Twelve phenolic acids have been identified from S. collina , such as vanillic acid, ferulic acid, salicylic acid, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings therefore suggest a revised procedure incorporating metabolomics analysis for future assessment of GM crops in order to establish substantial equivalence, a central aspect of the risk assessment process 27 . While acetyl-tryptophan is a naturally occurring metabolite found in numerous plant species, including Arabidopsis, Salsola collina, Glycine max, Solanum lycopersicum, Cocos nucifera, and Ginkgo biloba 28,29 , to the best of our knowledge, acetyl-aminoadipate has never been reported as an endogenous plant metabolite in non-transgenic plants. However, in line with our findings, a recent study showed that acetyl-aminoadipate accumulates in flowers of a BAR-containing mutant of Arabidopsis 30 .…”
Section: Transgenic Expression Of Enzymes Catalyzing a Variety Of Desmentioning
confidence: 92%